ANALISIS PERCOBAAN FAKTORIAL UNTUK MELIHAT PENGARUH PENGGUNAAN ALAT PERAGA BLOK ALJABAR TERHADAP PRESTASI BELAJAR ALJABAR SISWA - MIRAH MARIATI, NI PUTU AYU; SUCIPTAWATI, NI LUH PUTU; SARI, KARTIKA (E-Jurnal Matematika; Vol 2 No 2 (2013), 2013)
The experimental design was applied in research in many different fields of science, such as in education, as used in this study. Block algebra visual aids is a visual aids in the form of the geometry model used to concretize understanding the variables and constants in the algebra which is an abstract concept. This visual aids are used as a basis for factoring algebraic forms. In connection with this, the aims of this research is to determine the effect of the application of algebra block in student academic achievement in class VII in the field of algebra in schools categorized as private, SSN ( Sekolah Standar Nasional ) and the previously categorized RSBI ( Rintisan Sekolah Bertaraf Internasional ). The method of analysis used in this study was two-factor experimental design in a randomized block design. The results showed that the academic achievement of students in the field of algebra after learning with block algebra visual aids obtained better than the academic achievement of students who received learning without using block algebra visual aids . Moreover, it also shows that the categories of schools have a significant effect on student achievement.
Keywords: analysis of variance; experiments design; block algebra visual aids